Morphological Characteristics And Wear Mechanism Of Recycled Carbon Fibre Prepreg Reinforced Polypropylene Composites - Mohamad, Noraiham; Abd Latiff, Anisah; Liew, Pay Jun; Kasim, Mohd Shahir; Abd Razak, Jeefferie; Ab Maulod, Hairul Effendy; Qumrul Ahsan (Penerbit Akademia Baru, 2021)
The polypropylene (PP) reinforced with recycled carbon fibres (rCF) was successfully produced using a Haake internal mixer via melt compounding. The compounding was performed at 180°C, rotor speed of 50 rpm and compounding period of 10 minutes. The standard samples for the pin on disc testing were prepared using injection moulding. The effect of rCF filler loadings of 0.5, 1, 3, 5, 7, 10, 13, 15 and 20 wt% was studied for the tribological properties. The results were compared with 100% PP. The morphological behaviours for the effect of low and high fibre loadings were observed using scanning electron microscopy analyses.The composites with low carbon fibre loading of up to 3 wt% imposed higher resistance to dry sliding friction. In contrast, the increment of fibre loading at 5 wt% to 20 wt% decreased the wear rate of the composites due to patch film and transfer film formation. The wear mechanism of the composites for different fibre loading was graphically sketched from morphological observation. As the conclusions, the composites showed promising self-lubricating properties, capable of wear reduction with significant physical and mechanical properties.